Religiosity as a Moderator of the Effect of Organizational Commitment and Job Satisfaction on Employee Performance at Bappeda in Greater Malang - M. Jamal Abdul Nasir; Ali Hanafiah; Farah Adiba (Syntax Corporation Indonesia, 2025)
In the face of global and national demands for effective public institutions, enhancing civil servant performance is critical. This study examines the influence of organizational commitment and job satisfaction on employee performance at Bappeda in Greater Malang, with religiosity as a moderating variable. This study employed an explanatory research design to test the hypotheses regarding the influence of organizational commitment and job satisfaction on employee performance, with religiosity as a moderating variable. The population consists of all civil servants (except heads) of BAPPEDA in Malang Raya, including: Malang Regency Government, Malang City Government, and Batu City Government, totaling 134 employees. The data were collected through a census rather than sampling because the population was relatively small and to avoid sampling risks. Primary data related to the research variables were collected through Google Forms, sent directly to respondents via WhatsApp. Using an explanatory research approach, the collected data were tested for validity, reliability, and classical assumptions, then analyzed using multiple linear regression moderation. The results of this study prove that: first, organizational commitment has a significant positive effect on employee performance; second, job satisfaction has a significant positive effect on employee performance; third, religiosity can significantly moderate the positive effect of organizational commitment on employee performance; and fourth, religiosity can significantly moderate the positive effect of job satisfaction on employee performance.